Is Climate Change Affecting the Monsoon Months in Pune, India? - Shah, Shalaka; Londhe, Shreenivas (International Journal of Hydrology Research, 2022)
It is the need of the hour to study the changes occurring in the future rainfall trends for the Pune metropolitan region. General Circulation Models (GCMs) are used to study the variations in the climatic conditions occurring in the near and far future. GCMs yield the values of the required parameters over specific grid points which are not location specific and need to be downscaled. The current study suggests Artificial Neural Networks (ANN) as a tool for statistical downscaling. 5 precipitation causative parameters were mined from 5 GCMs each and then used as input to the neural networks, with the observed historical monthly cumulative precipitation as output. The best model was then used estimate the rainfall that would occur in the near future for Pune. The future rainfall analysis showed that the intensity of rainfall seems to be increasing for the non-monsoon months and decreasing for the monsoon months.